2021
DOI: 10.1017/s0954579420002230
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo evaluation of growth mixture modeling

Abstract: Growth mixture modeling (GMM) and its variants, which group individuals based on similar longitudinal growth trajectories, are quite popular in developmental and clinical science. However, research addressing the validity of GMM-identified latent subgroupings is limited. This Monte Carlo simulation tests the efficiency of GMM in identifying known subgroups (k = 1–4) across various combinations of distributional characteristics, including skew, kurtosis, sample size, intercept effect size, patterns of growth (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…This may negatively impact our data quality. Third, the use of LGMM can sometimes identify the wrong number of groups according to the levels of skew, kurtosis, intercept effect size, and group proportions (Depaoli et al, 2019; Shader & Beauchaine, 2021). Following recommendations by Nylund-Gibson and Choi (2018), we excluded solutions with infrequent classes (<5%) even when some fit indices may support solutions with more classes, because small classes tend to be unstable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may negatively impact our data quality. Third, the use of LGMM can sometimes identify the wrong number of groups according to the levels of skew, kurtosis, intercept effect size, and group proportions (Depaoli et al, 2019; Shader & Beauchaine, 2021). Following recommendations by Nylund-Gibson and Choi (2018), we excluded solutions with infrequent classes (<5%) even when some fit indices may support solutions with more classes, because small classes tend to be unstable.…”
Section: Discussionmentioning
confidence: 99%
“…However, we selected the two-class solution as optimal because subsequent class solutions had at least one class with low prevalence (< 5%). The two classes had reasonably large intercept effect sizes (Cohen's d = 1.55) easing concern of non-normal data driving grouping solutions according to simulation studies (Depaoli et al, 2019;Shader & Beauchaine, 2021). All of the selected models produced the best AIC and SSABIC among models without any class of low prevalence (<5%).…”
Section: Latent Growth Mixture Modelingmentioning
confidence: 95%
See 1 more Smart Citation
“…Females have been shown to be disproportionately impacted by exposure to online sexual contents (Kohut & Štulhofer, 2018) and have been more likely to be classified as high-risk internet users as compared to males (Victorin et al, 2020). Lastly, recent simulation studies (Depaoli et al, 2019;Shader & Beauchaine, 2021) indicated that group identification in LGMM can be impacted by non-normally distributed data. However, this concern is attenuated when intercept effect sizes are large, which is the case in the present study (e.g., intercept effect size of resilient and chronic: Cohen's d = 1.02).…”
Section: Discussionmentioning
confidence: 99%
“…However, this concern is attenuated when intercept effect sizes are large, which is the case in the present study (e.g., intercept effect size of resilient and chronic: Cohen's d = 1.02). Given that LGMM has been shown to be more effective when intercept effect sizes were large (Shader & Beauchaine, 2021), examining the two latent groups with the least (i.e., resilient) and most (i.e., chronic) prevalent PTSS avoids differentiating latent groups that were potentially artifacts of the methodology. However, since the non-normal distribution of PTSS in the present study (range of skewness Time 1-Time 3 = 0.48-0.69, range of kurtosis Time 1-Time 3 = 2.11-2.32) remains a concern for class misidentification (Depaoli et al 2019), it is critical to consider this limitation when interpreting findings.…”
Section: Discussionmentioning
confidence: 99%